Low folate biomarker concentrations are associated with increase the risk and severity of periodontitis in adults: A cross–sectional study based on the National Health and Nutrition Examination Survey 2009–2014 - Zhao, Lai-Xi; Hu, Cheng-Yang; Li, Zhen-Hua; Shao, Meng-Ci; Liu, Jia-Jia; Yan, Xiao-Rong; Li, Jiong; Xu, Wen-Hua; Zhang, Xiu-Jun (Nutrition research (New York, N.Y.), 2025)
•Folate biomarkers are linearly and negatively associated with adult periodontitis.•The association remains stable in populations with different characteristics.•Folate biomarkers may aid in surveillance and prevention of adult periodontitis. We sought to test the hypothesis that adult folate biomarker concentrations are negatively associated with the risk and severity of periodontitis. Data were pooled from the National Health and Nutrition Examination Survey (NHANES) 2009 to 2014. A total of 9252 dentate adult subjects aged 30 years and older who received a periodontal examination and had complete folate biomarker data were included in the analysis. Both logistic regression and linear regression models were built to analyze the associations between folate biomarker concentrations and periodontitis, followed by multisubgroup and sensitivity analyses. In addition, restricted cubic spline models were applied to observe the shape of the associations. We found negative associations between serum folate and periodontitis status (odds ratio [OR] = 0.775, 95% CI: 0.691-0.869), periodontal probing depth (PPD) (β = -0.048, 95% CI: -0.069 to -0.027), and clinical attachment loss (CAL) (β = -0.061, 95% CI: -0.098 to -0.025). A negative association was also found between red blood cell folate and periodontitis status (OR = 0.727, 95% CI: 0.613-0.861), PPD (β = -0.055, 95% CI: -0.086 to -0.024), and CAL (β = -0.084, 95% CI: -0.128 to -0.040). Subgroup and sensitivity analyses showed robust results. Restricted cubic spline models demonstrated significant linearity for associations. Folate biomarker concentrations were negatively associated with periodontitis in adults aged 30 years and older, indicating that folate may have a restrictive effect on the risk and severity of periodontitis. This finding may provide a clinical target for preventive and interventional measures to promote periodontal nutrition and health. The study investigated the association between folate biomarker concentrations and periodontitis using data on laboratory tests, questionnaires, dietary recalls, and periodontal examination of samples from the National Health and Nutrition Examination Survey 2009 to 2014. We found that a low concentration of folate biomarkers was associated with poorer periodontal status in adults. The findings may be helpful in studying clinical targets and treatment or prevention strategies for periodontitis. [Display omitted]